Ultrathin Phosphate‐Modulated Co Phthalocyanine/g‐C3N4 Heterojunction Photocatalysts with Single Co–N4 (II) Sites for Efficient O2 Activation - Chu, Xiaoyu; Qu, Yang; Zada, Amir; Bai, Linlu; Li, Zhijun; Yang, Fan; Zhao, Lina; Zhang, Guiling; Sun, Xiaojun; Yang, Zhao‐Di; Jing, Liqiang (Advanced science, 2020)
Realization of solar‐driven aerobic organic transformation under atmospheric pressure raises the great challenge for efficiently activating O2 by tailored photocatalysts. Guided by theoretical calculation, phosphate groups are used to induce the construction of ultrathin Co phthalocyanine/g‐C3N4 heterojunctions (CoPc/P‐CN, ≈4 nm) via strengthened H‐bonding interfacial connection, achieving an unprecedented 14‐time photoactivity improvement for UV–vis aerobic 2,4‐dichlorophenol degradation compared to bulk CN by promoted activation of O2. It is validated that more •O2− radicals are produced through the improved photoreduction of O2 by accelerated photoelectron transfer from CN to the ligand of CoPc and then to the abundant single Co–N4 (II) catalytic sites, as endowed by the matched dimension, intimate interface even at the molecular level, and high CoPc dispersion of resulted heterojunctions. Interestingly, CoPc/P‐CN also exhibits outstanding photoactivities in the aerobic oxidation of aromatic alcohols. This work showcases a feasible route to realize efficient photocatalytic O2 activation by exploiting the potential of ultrathin metal phthalocyanine (MPc) assemblies with abundant single‐atom sites. More importantly, a universal facile strategy of H‐bonding‐dominating construction of MPc‐involved heterojunctions is successfully established. Ultrathin phosphate‐modulated Co phthalocyanine/g‐C3N4 heterojunctions are successfully fabricated for effective photocatalytic O2 activation via phosphate‐induced strengthened H‐bonding interfacial connection, as driven by density functional theory calculation. The accelerated charge kinetics from g‐C3N4 to the ligand of CoPc and then to the abundant single Co–N4 (II) catalytic sites for O2 is evidenced to contribute to the outstanding photocatalytic performances.